Nanomaterials in asphalt cement: Exploring their single and combined effects on the physical and rheological properties - Amjad H. Albayati; Mazen J. Al-Kheetan; Mustafa M. Moudhafar; Ahmed M. Mohammed (Results in Engineering)
Pavement deterioration due to rutting, fatigue, and thermal cracking poses significant challenges to road infrastructure. Traditional asphalt modifiers often fall short in addressing these issues, leading to growing interest in advanced materials such as nanomaterials. This study investigates the individual and combined effects of three nanomaterials: nano-titanium dioxide (NT), nano-alumina (NA), and nano-silica (NS), on the physical and rheological properties of asphalt binders when used in dosages of 0%, 1%, and 2% by the weight of asphalt. This study aims to enhance asphalt performance and contribute to international research efforts focused on pavement durability. The experimental program evaluated the penetration, softening point, mass loss after aging, and viscosity properties, in addition to rutting and fatigue resistance through dynamic shear rheometer (DSR) tests. Scanning electron microscopy (SEM) was also employed to observe morphological changes. Results showed that 2% NA reduced penetration by 3.19%, while 2% NS increased the softening point by 2.41%. The combination of NA and NS had the highest effect on the softening point (F = 6.21, p = 0.008). NA and NT reduced mass loss, with 2% NA lowering it from 0.432% to 0.201%. Viscosity increased by 17.4% with 2% NA, while the NA and NS combination had the most significant overall impact (F = 44.78, p = 0.000). At higher temperatures, 2% NA was the most effective in reducing aging. Optimizing the use of NA and NS, either individually or combined, offers the best improvements in binder stiffness, thermal stability, and aging resistance.